2010
DOI: 10.2967/jnumed.110.080226
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intraperitoneal Radioimmunotherapy of Small Peritoneal Carcinomatosis Using High Activities of Noninternalizing 125I-Labeled Monoclonal Antibodies

Abstract: We assessed the efficiency and toxicity of brief intraperitoneal radioimmunotherapy using high activities of 125 I-labeled monoclonal antibody (mAb) in the treatment of small-volume peritoneal carcinomatosis. Methods: Brief intraperitoneal radioimmunotherapy consisted of a 185-MBq (740 MBq/mg) intraperitoneal injection of 125 I-35A7 (an anti-carcinoembryonic antigen mAb) into athymic nude mice 4 d after peritoneal tumor xenografting and, after 1 h, abundant washing of the peritoneal cavity with saline solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Two additional studies were recently published by members of Pouget ' s group (Santoro et al 2009, Boudousq et al 2010) that build upon the earlier studies discussed above. Santoro et al (2009) came to the conclusion that RIT using the Auger emitter, 125 I, should only be considered for treatment of small tumors, reporting some effi cacy in the treatment of small-volume peritoneal carcinomatosis.…”
Section: Application Of Molecularly Targeted Therapeutics/ Applying Pmentioning
confidence: 92%
See 1 more Smart Citation
“…Two additional studies were recently published by members of Pouget ' s group (Santoro et al 2009, Boudousq et al 2010) that build upon the earlier studies discussed above. Santoro et al (2009) came to the conclusion that RIT using the Auger emitter, 125 I, should only be considered for treatment of small tumors, reporting some effi cacy in the treatment of small-volume peritoneal carcinomatosis.…”
Section: Application Of Molecularly Targeted Therapeutics/ Applying Pmentioning
confidence: 92%
“…Although this approach was primarily presented as an imaging approach (Cornelissen et al 2011a), the authors speculate on possible therapeutic roles for targeting DNA double-strand breaks with their Auger emitter labeled anti-γ H2AX compound. layers has been reported (Boudousq et al 2010). 125 I-antiCEA has been found to be eff ective with low toxicity in the therapy of small volume peritoneal carcinomatosis after cytoreductive surgery and is a viable alternative to α and β emitters.…”
Section: Application Of Molecularly Targeted Therapeutics/ Applying Pmentioning
confidence: 96%
“…This is especially important in cases such as disseminated intraperitoneal tumor where it is impossible to measure tumor dimensions (38,39). Bioluminescence imaging of disseminated peritoneal tumor has been used to study response to therapies such as radioimmunotherapy with I 125 -labeled antibodies (40) and conjugates between daidzein and alliinase (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a ''brief intraperitoneal RIT'' approach involving high dose administration of noninternalizing 125 I-35A7 was described. 19 In contrast to the previous study where 37 MBq 125 I-labeled MAbs were administered intravenously, in ''brief intraperitoneal RIT'' 185 MBq of radioimmunoconjugate was administered intraperitoneally and the unbound antibody was removed 1 hour postadministration by flushing the peritoneal cavity with saline. SPECT imaging indicated that after flushing the radioiodine signal was associated only with the intraperitoneal tumors.…”
Section: Optimal Radionuclides and Antibody Characteristics For Intramentioning
confidence: 99%
“…Several studies have been undertaken to identify the most suitable radionuclides (b-, a-or auger-emitters), antibody formats [F(ab¢) 2 IgG, IgM] and types (internalizing vs. noninternalizing), and evaluating the toxicity of radionuclides on the peritoneal membrane. [18][19][20][21][22][23][24] In the context of intraperitoneal RIT involving a-particle emitters, recent studies have also explored their utility in several ways: multiple administrations 25 and the impact of using variable specific activities 26 ; compared the efficacy of intraperitoneal RIT with pretargeted intraperitoneal RIT 27 ; and investigated the impact of antibody glycosylation on efficacy. 28 …”
Section: Rit and Minimal Residual Diseasementioning
confidence: 99%